Northeast Asian approches to Algeria - PARK, Jeong-Sun (KDI School, 2015)
While much has been written about Asian approaches of development cooperation to Africa, studies on Asian approaches to Algeria remain unknown. Asian approaches.based on perspectives different from those of Europe.would be valuable for Algeria to make it possible to apply Asian successful economic growth models to Algeria. This research attempted to find out whether infrastructure development is linked to economic growth in Algeria and whether Northeast Asian countries’ roles are different for the infrastructure development from the development cooperation standpoint. As methodology, the main data were collected through on-line interviews and archives from ODA-related international organizations. As Algeria is located at the aid-exit stage thanks to the oil and gas export revenue, this research focuses more on infrastructure development which is the foundation for future economic growth by including private sector cooperation in the development cooperation, as well as development cooperation through aid agencies. Northeast Asian countries’ approaches to Algeria are concerned with their own strengths which has led successful economic growth. China has been leading “Construction Boom” in Algeria on the basis of low cost, rapid progress and capital strength. Japan has been focusing on energy sector and road construction sector in Algeria on the basis of high quality, cutting-edge and economic technology. And South Korea has been engaging in diverse infrastructure sectors in Algeria on the basis of good quality in terms of cost-effectiveness. On the other hand, their weaknesses in the Algerian local business environment are left in abeyance for the sustained and enhanced cooperation between China-Japan-South Korea and Algeria. China has weaknesses such as weak transparency and low quality. Japan has weak spots such as high price and lack of flexibility. South Korea has weakness such as relatively weak price comparativeness comparing to China or India. In order to switch from an oil-dependent country to an oil-based growing country, further researches on relations between these Northeast Asian countries and Algeria with regards to the industrial diversification will be needed to overcome two main barriers in Algeria: oil dependency and youth unemployment. This study on cooperation between China-Japan- South Korea and Algeria in the infrastructure sector would be the basis for the future cooperation between them in the future diverse industries.
Thesis(Master) --KDI School:Master of Public Policy,2015